Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1073/pnas.93.15.7732
|View full text |Cite
|
Sign up to set email alerts
|

Substitution rate calibration of small subunit ribosomal RNA identifies chlorarachniophyte endosymbionts as remnants of green algae.

Abstract: November 29, 1995) ABSTRACT Chlorarachniophytes are amoeboid algae with chlorophyll a and b containing plastids that are surrounded by four membranes instead of two as in plants and green algae. These extra membranes form important support for the hypothesis that chlorarachniophytes have acquired their plastids by the ingestion of another eukaryotic plastidcontaining alga. Chlorarachniophytes also contain a small nucleus-like structure called the nucleomorph situated between the two inner and the two outer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
99
0
3

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(109 citation statements)
references
References 36 publications
(41 reference statements)
7
99
0
3
Order By: Relevance
“…Cryptosporidium spp. and other Apicomplexa are thought by some researchers to have diverged from a dinoflagellate-like, rather than zooflagellate, ancestor (Van de Peer et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Cryptosporidium spp. and other Apicomplexa are thought by some researchers to have diverged from a dinoflagellate-like, rather than zooflagellate, ancestor (Van de Peer et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Variable evolutionary rates generate artificial groupings in the eukaryotic molecular tree (36), because of LBA. Taking into account among-site rate variation through a ⌫ law is known to alleviate the LBA problem (37), which has been successfully shown in the case of the eukaryotic rRNA tree (38). Unfortunately, the covarion-like structure of molecular markers could limit the success of this approach (13).…”
mentioning
confidence: 99%
“…It has been shown previously that the transversion analysis is less sensitive to the substitutional bias (Van de Peer et al, 1996). Again, a tree constructed on the basis of evolutionary distances computed according to Van de Peer et al (1996) shows a tree topology similar to that shown in Fig.…”
Section: Phylogenetic Analyses Using Nucleotide Sequencesmentioning
confidence: 80%
“…Since the existence of two different mitochondrial genomes within a single cell was quite implausible, the origin of the 35 kb DNA circle had began to be intensively studied. Based on the close phylogenetic relationship between apicomplexans and dinoflagellates (Cavalier-Smith, 1993; Van de Peer et al, 1996) and the fact that the 35 kb circular molecule has a gene content similar to that of chloroplasts, hypothesis that it represents a highly reduced plastid genome started to emerge. The DNA circle was localized in situ to a multimembranous structure, previously described as a 'spherical body' (e.g.…”
Section: Introductionmentioning
confidence: 99%